Maritime security in the Indo-Pacific perspectives from China, India, and the United States - Malik, Mohan (Rowman & Littlefield, 2014)
Maritime Security in the Indo-Pacific opens by introducing the Indo-Pacific and outlining the roles of China, India, and the United States in various maritime issues in the region. This volume develops common approaches by focusing on geopolitical challenges, transnational security concerns, and multilateral institution-building and cooperation.